The Visual Metaphor of Disability in Sarah Leavitt's Graphic Memoir Tangles: A story about alzheimer's, my mother, and me - Renata Lucena Dalmaso (Ilha do Desterro)
Borrowing George Lakoff and Mark Johnson’s Conceptual Metaphor theory, and its implications for the study of visual metaphors, this article seeks to investigate the representation of the disabled body in the graphic memoir Tangles: A Story about Alzheimer’s, My Mother, and Me (2012), by Sarah Leavitt. The genre of comics, as a cross-discursive medium, is prolific in the use of visual metaphor as a narrative technique and Leavitt’s graphic memoir, in particular, employs visual metaphor in the depiction of her mother’s experience of Alzheimer’s, as someone slowly distancing herself from her family.